GENTLEMAN’S RESTRICTED CODES AND ELABORATED CODES IN THE “KINGSMAN: THE GOLDEN CIRCLE” MOVIE - Domisianus, Toar Dayan; Ena, Ouda Teda (BASIS (Bahasa dan Sastra Inggris), 2022)
The present study aims to analyse the content of the Kingsman: The Golden Circle movie (2017). The use of restricted codes and elaborated code by the main character Gary ‘Eggsy’ Unwin in the movie and how they convey the concept of English gentleman was investigated by applying the descriptive qualitative method. The movie script and the scenes in the movie were the data that were being analysed. Data were collected through observation using a non-participatory technique. The data were analysed using the Barthesian semiotic analysis method. It was found that there were seven types of restricted codes namely secrecy, intimacy, novelty, jocularity, sympathy, expressiveness, and nominative. While the use of elaborated code was found in the forms of verbal and non-verbal communications. The findings in this research showed that the main character employed the restricted codes and the elaborated codes to express proximity and to convey the idea of the new English gentleman of the 21st century.